2019
DOI: 10.1089/acu.2018.1327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auricular Acupuncture on Propofol Induction Dose: Could Vagus Nerve and Parasympathetic Stimulation Replace Intravenous Co-Induction Agents?

Abstract: Objective: Auricular acupuncture, through a combination of several points, can produce sedative and analgesic effects. The aim of this study was to compare the induction dose of propofol required to obtain a loss of response to verbal commands, with and without a preoperative combination of auricular points. Materials and Methods: This study involved American Society of Anesthesiologists physical status I and II patients, ages 18-65, of either sex, having elective ambulatory surgery (digestive or gynecologic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[ 23 ] Acupuncture can provide clinical benefits in the perioperative period, especially for reducing preoperative anxiety, as well as postoperative pain, nausea and vomiting. [ 24 ] Previous study indicated that acupuncture might be tolerated and accepted in adolescents suffering from anxiety, with few side effects and adverse events have been reported. [ 11 ] Therefore, a systematic review of the effectiveness of acupuncture in the treatment of preoperative anxiety in adolescents is necessary to provide evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] Acupuncture can provide clinical benefits in the perioperative period, especially for reducing preoperative anxiety, as well as postoperative pain, nausea and vomiting. [ 24 ] Previous study indicated that acupuncture might be tolerated and accepted in adolescents suffering from anxiety, with few side effects and adverse events have been reported. [ 11 ] Therefore, a systematic review of the effectiveness of acupuncture in the treatment of preoperative anxiety in adolescents is necessary to provide evidence.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% patients undergoing scheduled for elective surgery developed preoperative anxiety [23] . Acupuncture can provide clinical benefits in the perioperative period, especially for reducing preoperative anxiety, as well as postoperative pain, nausea and vomiting [24] . Previous study indicated that acupuncture might be tolerated and accepted in adolescents suffering from anxiety, with few side effects and adverse events have been reported [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Published articles suggest that stimulation of auricular points might result in reduction of medications necessary for induction of the anesthesia. [2][3][4][5] We needed to research and find a specific ear point corresponding to COVID-19. To assist with this task, we demonstrated in previous research that auricular causative diagnosis (ACD) is an objective tool that allows one to visualize the status of all organs, provides a functional diagnosis, and shows the origin of the pathology.…”
mentioning
confidence: 99%